2018
DOI: 10.1159/000490012
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin2 Regulates the Differentiation and Function of Cardiac Progenitor Cells via the Notch Signaling Pathway

Abstract: Background/Aims: The transplantation of cardiac progenitor cells (CPCs) improves neovascularization and left ventricular function after myocardial infarction (MI). The bone morphogenetic protein antagonist Gremlin 2 (Grem2) is required for early cardiac development and cardiomyocyte differentiation. The present study examined the role of Grem2 in CPC differentiation and cardiac repair. Methods: To determine the role of Grem 2 during CPC differentiation, c-Kit+ CPCs were cultured in differentiation medium for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…For GREM2 , subjects carrying the minor allele had a greater change in SUA on allopurinol and were significantly more likely to reach and maintain rheumatologist‐recommended SUA concentrations ( Figure ). GREM2 is a secreted antagonist of BMP that has been shown to play a role in cell differentiation and limit inflammation after myocardial infarctions in mice . GREM2 has been previously shown to be upregulated in glomeruli of rats with diabetic kidney disease, and dysregulation of its target, BMP, has been linked to diabetic kidney nephropathy and cardiovascular disease, suggesting a role for GREM2 in the development of common gout sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For GREM2 , subjects carrying the minor allele had a greater change in SUA on allopurinol and were significantly more likely to reach and maintain rheumatologist‐recommended SUA concentrations ( Figure ). GREM2 is a secreted antagonist of BMP that has been shown to play a role in cell differentiation and limit inflammation after myocardial infarctions in mice . GREM2 has been previously shown to be upregulated in glomeruli of rats with diabetic kidney disease, and dysregulation of its target, BMP, has been linked to diabetic kidney nephropathy and cardiovascular disease, suggesting a role for GREM2 in the development of common gout sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…GREM2 is a secreted antagonist of BMP that has been shown to play a role in cell differentiation and limit inflammation after myocardial infarctions in mice. [21][22][23] GREM2 has been previously shown to be upregulated in glomeruli of rats with diabetic kidney disease, and dysregulation of its target, BMP, has been linked to diabetic kidney nephropathy and cardiovascular disease, 24,25 suggesting a role for GREM2 in the development of common gout sequelae. Interestingly, GREM2 has not been shown to associate with baseline SUA or gout, suggesting that its role in improving allopurinol response is pharmacologic, related to allopurinol's effects on uric acid lowering.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling plays an important role in regulating CPC differentiation [19][20][21][22]. Moreover, we have recently shown that 3D CPCs improve RV vessel density in a RVHF rat model in a Notchdependent manner [5].…”
Section: A Priori Prediction Of the Effect Of Notch Inhibition On Exomentioning
confidence: 99%
“…To elaborate, embryogenesis is mediated by the activity of extracellular proteins such as chordin, noggin, cerberus, and dan family protein gremlin2. Amongst these antagonists, gremlin2 acts as the strongest BMP ligand inhibitor [112]. Alongside, chordin is involved in neural induction and mesoderm dorsalization during embryonic development.…”
Section: Inhibitors Of Bmp-7mentioning
confidence: 99%